Rural Women in Occupational Diversification: A Strategy for Economic Empowerment - E. N. Mbah; E. T. Yanjoh; Jabil, I. Yerima (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
The study centered on rural women in occupational diversification: A strategy for economic empowerment. Rural women are engaged in occupational diversification in order to be economically empowered since farming is rain-fed and seasonal. This is to enable them to be financially strong to take care of their family responsibilities and ensure household food security during off-season periods. In addition, rural women’s diversification into various occupations could be attributed to a number of factors, namely; overcoming risks against crop failures, seasonality of farming activities, source of additional income, shortage of farm labor, improved transport facilities, increase in family responsibilities as well as proximity to urban markets. Rural women continue to struggle with dual responsibilities of economic production and domestic labor and most of them are confronted by poverty, illiteracy, high health risks, in adequate access to productive resources, among others. The study recommends that government policies and programs should promote the development of human capital by equipping rural women with the necessary skills to work in various on-farm and non-farm occupations. It also highlights the need for adequate formulation and implementation of policies that will meet economic empowerment needs of rural women who are engaged in occupational diversification.